Phytochemical Screening and In Vitro Antibacterial Activity of Swietenia mahagoni Leaf Extract against Streptococcus mutans: A Promising Natural Approach for Caries Prevention - Muharraran, Firdha; Florenly; Ivan Melka (HM Publisher, 2025)
Background: Dental caries, primarily caused by Streptococcus mutans, is a prevalent oral health issue. The rise of antibiotic resistance and side effects of synthetic antimicrobials have fueled the search for plant-derived alternatives. Swietenia mahagoni (mahogany) leaves, traditionally used for medicinal purposes, exhibit potential antibacterial properties. This study investigated the phytochemical composition and in vitro antibacterial activity of S. mahagoni leaf extracts against S. mutans. Methods: S. mahagoni leaves were collected, processed, and extracted using ethanol. Phytochemical screening identified alkaloids, tannins, flavonoids, and saponins. Antibacterial activity was assessed through the agar well diffusion method against S. mutans, using various extract concentrations (25%, 50%, 75%) and chlorhexidine as a positive control. Inhibition zone diameters were measured to determine antibacterial efficacy. Results: Phytochemical analysis confirmed the presence of alkaloids, tannins, flavonoids, and saponins in the S. mahagoni leaf extract. The extract demonstrated significant antibacterial activity against S. mutans at all concentrations. The highest concentration (75%) showed the largest inhibition zone (18.07 ± 0.37 mm), significantly larger than those of lower concentrations and the positive control (chlorhexidine, 13.87 ± 0.21 mm). Conclusion: S. mahagoni leaf extract exhibits substantial antibacterial activity against S. mutans, likely due to its diverse phytochemical content. These findings suggest its potential as a natural anti-caries agent. Further research is needed to explore its use in developing novel oral health products.